Perancangan dan Implementasi Iklan Konten Video Cinematic Promotion Coffee Shop Renjana - Hendi Sama; Maria Ulfa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Renjana Kopi is one of the Coffee Shops in Batam that sells contemporary coffee and non-coffee drinks. However, Renjana Kopi does not yet have a promotional media in the form of a promotional video that can introduce it to the wider community. Promotional video is a form of communication of marketing activities or advertisers, and disseminating product information to consumers who want to persuade. Therefore, we need a promotional media in the form of a video in a cinematic concept that can provide information and advantages of Renjana Kopi. The methods used are direct interviews with the owner of Renjana Kopi, direct observation to the location, and literature study. The results of this research will be implemented on Renjana Kopi's social media account via Instagram. The promotional video can increase sales, and is useful as a medium of information for the public.